Simulation of Phase Change Material Solidification for High-Performance Aero-Thermal Energy Storage - Muhamad Noor, Izzul Nisa’; Taib, Ishkrizat; Abd Razak, Mohd Syahir; Mohamad Haniff, Mohammad Hasiff; Ismail, Norhasikin (Progress in Aerospace and Aviation Technology, 2025)
Phase Change Materials (PCM) can be used in aerospace thermal management systems due to their ability to absorb and release large amounts of latent heat during phase transitions, making them effective for controlling temperature fluctuations in high-performance aero components. The research paper examines the solidification of paraffin wax PCM in a rectangular enclosure through the computational fluid approach provided by ANSYS Fluent. These three geometrical regions comprised Geometry 1, whose size was 150 mm x 100 mm; Geometry 2, of 200 mm x 150 mm; and Geometry 3, of 250 mm x 200 mm, and were examined under three sets of thermal boundaries, which were 363 K-294 K, 380 K-300 K, and 400 K-310 K. The transient simulation with the enthalpy-porosity approach was run to assess the temperature distribution, the pressure profiles, and the phase change advancement. The findings indicate that increased geometry sizes and greater thermal differences favor a stronger natural convection and a rapid solidification. The numerical model demonstrates the correlation between design parameters and PCM behavior, allowing for the optimization of TES systems’ thermal performance.